الإجراءات الإستثنائیة للبحث والتحري عن الجرائم في التشریع الجزائري - هاشمي وهيبة (My University, 2016)
The methods of crime have increased substantially, such as organized transnational crime, drug trafficking, money laundering, terrorism, cybercrime, crimes against property and crimes of corruption. The authors use various means to hide the traces and mislead investigators. To cope with this development, the Algerian legislature has included in the Code of Criminal Procedure -by 2006 amendment- as well as in other laws, many procedures such as : interception of correspondence, sound systems and image attachments, monitoring of electronic communications, electronic surveillance and infiltration. This raises several issues relating to abuses by security forces during their investigation, and their impact on the functioning and effectiveness of investigations and the principle of procedural legitimacy. For that, I pose the following problem: What is the extent of the effectiveness of exceptional measures against crime compared to violations of the rights and individuals freedoms they induce, and in front of the rights of protection of individual freedoms of the accused in a manner as to not conflict with the interests of the group? To address this problem, I divided this subject into two chapters. I discussed in the first chapter: research, investigation and exceptional measures. In the second chapter, the guarantees that accompany the exceptional measures, and the consequences of their violation.